Economics of resource recovery from sugar cane and distillery industries - Kaul S.N.; Nandy T.; Sharma Y. (My University, 2025)
Cane molasses based distilleries are amongst the major water polluting industries in India. The distilleries are mainly engaged in the manufacture of alcohol by fermentation of molasses using yeast culture followed by distillation. The spentwash generated from the distillation of fermenter wash is highly acidic (pH is less than 5.0) with high concentration of organics, viz BOD and COD being more than 50 kg/m3, and 90 kg/m3, respectively, and suspended solids concentration above 2 kg/m3. The paper highlights the appropriate waste management option comprising biomethanation followed by concentration (evaporation technology) through multiple effect evaporators, and utilization of the concentrated effluent for biocomposting of pressmud (by-product from sugar industry) for production of biomanure thereby achieving zero effluent discharge, including cost analysis.